A community-based study on the prevalence and factors affecting smoking in Terengganu state, Malaysia, 2004 - Gyanchand Rampal, Lekhraj Rampal; Lekhraj Rampal, Sanjay Rampal; Md. Zain, Azhar; M. H., Kamil (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2006)
Introduction: It is estimated that 4.9 million people worldwide died in 2000 as a result of their addiction to nicotine, about half of them prematurely. This huge death toll is rising rapidly, especially in low and middle income countries where most of the world’s 1.2 billion tobacco users live. Objectives: This study aimed to determine (i) the prevalence of smoking among the community aged 18 and above in Terengganu state, and (ii) the relationship between smoking and age, sex, educational level, family and peer influence. Methods: A cross-sectional study design was used in this study and data was collected using a standardised pre-tested structured questionnaire. Results: The overall mean age of the respondents was 38.9 (95% CI= 37.7 – 40.2) years. The majority of the respondents were Malays (99.1%). Of the 653 respondents, 32.2% and 23.6% were ever and current smokers respectively. Of this, 211 ever smokers, 199 (94.3%) were males and only 12 (5.7%) were females. The prevalence of ever and current smokers for males was 73.2% and 53.7% respectively compared to the females (3.1% and 2.1% respectively). There was a significant association between smoking status and sex (p<0.001). The prevalence of ever smokers was lowest amongst respondents with college or university educational level. However, for current smokers, those with college or university education had the highest prevalence. The overall mean initiation age of ever smokers was 19.7 years (95% CI = 18.8 – 20.7). The mean initiation age for the males (19. 1 years) was significantly lower compared to 29.8 years for the females (p<0.001). The mean duration of smoking for the current smokers was 21.6 (95% CI= 19.1 – 24) years. There was also no significant difference in the mean duration of current smoking for males compared to the females (p = 0.5). The majority (93.4%) of the ever smokers started either because their friends asked them to try or they were trying for fun. The quit ratio was 27%. Conclusion : The prevalence of ever and current smokers in males is very high (73.2% and 53.7% respectively) compared with the females (3.1% and 2.1% respectively). The mean initiation age for the males (19. 1 years) was significantly lower compared to 29.8 years for the females (p<0.001).